2019
DOI: 10.1523/jneurosci.2954-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and White-Matter Compartment Models Reveal Selective Relations between Corticospinal Tract Microstructure and Simple Reaction Time

Abstract: The speed of motor reaction to an external stimulus varies substantially between individuals and is slowed in aging. However, the neuroanatomical origins of interindividual variability in reaction time (RT) remain unclear. Here, we combined a cognitive model of RT and a biophysical compartment model of diffusion-weighted MRI (DWI) to characterize the relationship between RT and microstructure of the corticospinal tract (CST) and the optic radiation (OR), the primary motor output and visual input pathways assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 123 publications
1
25
3
1
Order By: Relevance
“…We add to this body of work by confirming that not only that macrostructural damage to association tracts, but also projection tracts, have a role in memory function. Our unexpected finding regarding the relationship between WMH in projection white matter tracts, particularly the relationship between corticospinal tract and memory, deviates from previous DTI studies, which suggested a role of the corticospinal tract in sensorimotor functions rather than cognitive functions (Carter et al., 2012; Karahan et al., 2019). A plausible explanation of the relationship between corticospinal tract WMH and memory may simply be due to the tract's proximity to the lateral ventricles, where periventricular WMH reside and are known to be associated to memory (Munoz Maniega et al., 2019; Smith et al., 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…We add to this body of work by confirming that not only that macrostructural damage to association tracts, but also projection tracts, have a role in memory function. Our unexpected finding regarding the relationship between WMH in projection white matter tracts, particularly the relationship between corticospinal tract and memory, deviates from previous DTI studies, which suggested a role of the corticospinal tract in sensorimotor functions rather than cognitive functions (Carter et al., 2012; Karahan et al., 2019). A plausible explanation of the relationship between corticospinal tract WMH and memory may simply be due to the tract's proximity to the lateral ventricles, where periventricular WMH reside and are known to be associated to memory (Munoz Maniega et al., 2019; Smith et al., 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown lower CST integrity to be associated with worse perceptual speed in persons with older age, 57 but also higher neurite density in the CST to be associated with faster nondecision time in reaction time tasks, implying a more efficient network for voluntary actions. 58 In persons with relapsing-remitting multiple sclerosis, Riccitelli et al determined that lesions in the CST and FM are associated with poor SDMT performance. 59 Studies in patients with cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy have shown that damage of the left CST is associated with poor processing speed.…”
Section: Wmh Locations Are Associated With the Specific Subtypes Of Pmentioning
confidence: 99%
“…The accumulation process terminates when the activation of any accumulator reaches a response threshold B (B > A) and the choice corresponding to the winning accumulator is selected. The model prediction of RT (measured in seconds) is the sum of the duration of the accumulation process and a constant nondecision time T er , with the latter accounting for the latency associated with other processes including stimulus encoding and action execution (Brown and Heathcote 2008;Nunez et al 2019;Karahan et al 2019).…”
Section: A Cognitive Model Of Voluntary Decision-makingmentioning
confidence: 99%
“…During perceptual learning, the accumulation rate increases along with behavioral improvements (Jia et al 2018), while the non-decision time remains unchanged in the late stage of training (Zhang and Rowe 2014). Furthermore, the accumulation rate is associated with the individual differences in working memory (Schmiedek et al 2007) and attention (Nunez et al 2017), while the non-decision time is faster in individuals with higher diffusion MRI-derived neurite density in the corticospinal tract, the primary motor output pathway (Karahan et al 2019). Recent research showed that both parameters can be influenced by reward magnitude (Wagner et al 2020), and the current study will examine further whether reward probability and preference influence the two model parameters.…”
Section: Introductionmentioning
confidence: 99%